Inhibition of Dipeptidyl Peptidase-4 Impairs Ventricular Function and Promotes Cardiac Fibrosis in High Fat–Fed Diabetic Mice - Mulvihill, Erin E.; Varin, Elodie M.; Ussher, John R.; Campbell, Jonathan E.; Bang, K.W. Annie; Abdullah, Tahmid; Baggio, Laurie L.; Drucker, Daniel J. (Diabetes (New York, N.Y.), 2016)
Dipeptidyl peptidase-4 (DPP4) inhibitors used for the treatment of type 2 diabetes are cardioprotective in preclinical studies; however, some cardiovascular outcome studies revealed increased hospitalization rates for heart failure (HF) among a subset of DPP4 inhibitor–treated subjects with diabetes. We evaluated cardiovascular function in young euglycemic Dpp4−/− mice and in older, high fat–fed, diabetic C57BL/6J mice treated with either the glucagon-like peptide 1 receptor (GLP-1R) agonist liraglutide or the highly selective DPP4 inhibitor MK-0626. We assessed glucose metabolism, ventricular function and remodeling, and cardiac gene expression profiles linked to inflammation and fibrosis after transverse aortic constriction (TAC) surgery, a pressure-volume overload model of HF. Young euglycemic Dpp4−/− mice exhibited a cardioprotective response after TAC surgery or doxorubicin administration, with reduced fibrosis; however, cardiac mRNA analysis revealed increased expression of inflammation-related transcripts. Older, diabetic, high fat–fed mice treated with the GLP-1R agonist liraglutide exhibited preservation of cardiac function. In contrast, diabetic mice treated with MK-0626 exhibited modest cardiac hypertrophy, impairment of cardiac function, and dysregulated expression of genes and proteins controlling inflammation and cardiac fibrosis. These findings provide a model for the analysis of mechanisms linking fibrosis, inflammation, and impaired ventricular function to DPP4 inhibition in preclinical studies.